Sei sulla pagina 1di 3

# [1/(x+ 1)] dx

## very tough integral...!

the denominator is a sum of squares, thus it is not
factorable, therefore partial fraction method seems inapplicable;
nevertheless, you can apply it on condition that you
rearrange the integrand as follows:
add and subtract 2x at denominator, in order to complete
the square:
[1/ (x+ 2x +1 - 2x)] dx =
{1/ [(x+ 2x +1) - 2x]} dx =
{1/ [(x +1) - 2x]} dx =
now factor the denominator, viewing it as a difference
between two squares:
{1/ [(x +1) - (2x)]} dx =
{1/ {[(x +1) + (2x)] [(x +1) - (2x)]}} dx =
{1/ [(x + 2x +1)(x - 2x +1)]} dx =
well, this rearranged integrand is solvable by partial fractions:
so you have to find four real numbers A, B, C and D, so that:
1/ [(x +2x +1)(x -2x +1)] = (Ax + B) /(x +2x +1) + (Cx + D) /(x -2x +1)
1/ [(x +2x +1)(x -2x +1)] =
[(Ax + B)(x -2x +1) + (Cx + D)(x +2x +1)] / [(x +2x +1)(x -2x +1)]
equating the numerators:
1 = [(Ax + B)(x -2x +1) + (Cx + D)(x +2x +1)]
1 = Ax -2Ax + Ax + Bx -2Bx + B + Cx+ 2Cx+ Cx + Dx +2Dx + D
1 = (A + C)x + (-2A + B + 2C + D)x+ (A -2B + C +2D)x + (B + D)
| A + C = 0 A = - C A = 1/(22)
| -2A + B +2C+ D = 0 -2(- C)+ B +2C+ D = 0 22C + 1 = 0 C = -1/(22)
| A -2B + C +2D = 0 - C -2B + C +2D = 0 2D = 2B D = B B = (1/2)
| B + D = 1 D + D = 1 D = (1/2)
now, plugging in the found values, you get (see above):
1/ [(x +2x +1)(x -2x +1)] = (Ax + B) /(x +2x +1) + (Cx + D) /(x -2x +1)
1/ [(x +2x +1)(x -2x +1)] =
{[1/(22)]x + (1/2)} /(x +2x +1) + {[-1/(22)]x + (1/2)} /(x -2x +1)
factoring out [1/(22)] at both fractions:
1/ [(x +2x +1)(x -2x +1)] =
[1/(22)] [(x +2) /(x +2x +1)] + [1/(22)] [(-x +2) /(x -2x +1)]
therefore:
{1/ [(x + 2x +1)(x - 2x +1)]} dx =
{[1/(22)] [(x +2) /(x +2x +1)] + [1/(22)] [(-x +2) /(x -2x +1)]} dx =
breaking it up and taking the constants out:
[1/(22)] [(x +2) /(x +2x +1)] dx + [1/(22)] [(-x +2)} /(x -2x +1)] dx =
now, in order to change each numerator into the derivative
of the respective denominator, divide and multiply the first
integral by 2 and the second one by (-2), yielding:
[1/(22)](1/2) [2(x+2) /(x+2x+1)] dx+ [1/(22)](-1/2) [(-2)(-x+2)} /(x-2x+1)] dx =

[1/(42)] [(2x + 22) /(x+2x +1)] dx - [1/(42)] [(2x - 22)} /(x-2x +1)] dx =
then rewrite the numerators as:
[1/(42)] [(2x +2 +2) /(x+2x +1)] dx - [1/(42)] [(2x - 2 - 2)} /(x-2x +1)] dx =
and distribute them as:
[1/(42)] {[(2x +2)/(x+2x +1)] + [2 /(x+2x +1)]} dx [1/(42)] {[(2x - 2)/(x-2x +1)] - [2 /(x-2x +1)]} dx =
breaking it up,
[1/(42)] [(2x +2)/(x+2x +1)] dx + [1/(42)] [2 /(x+2x +1)] dx [1/(42)] [(2x - 2)/(x-2x +1)] dx + [1/(42)] [2 /(x-2x +1)] dx =
simplifying;
[1/(42)] [d(x+2x +1)] /(x+2x +1) + (1/4) [1 /(x+2x +1)] dx [1/(42)] [d(x-2x +1)] /(x-2x +1)] + (1/4) [1 /(x-2x +1)] dx =
[1/(42)] ln (x+2x +1) + (1/4) [1 /(x+2x +1)] dx - [1/(42)] ln (x-2x +1) +
(1/4) [1 /(x-2x +1)] dx =
[1/(42)] [ln (x+2x +1) - ln (x-2x +1)] + (1/4) [1 /(x+2x +1)] dx +
(1/4) [1 /(x-2x +1)] dx =
according to log properties,
[1/(42)] ln [(x+2x +1)/(x-2x +1)] + (1/4) [1/(x+2x +1)] dx +
(1/4) [1/(x-2x +1)] dx =
to solve the remaining integrals, you need to complete the
squares at denominators, since they aren't factorable;
more exactly, you have to attempt to change the denominators into {[f (x)]+ 1} form (which is
then integrable as arctan: {d[f(x)]} /{[f(x)] + 1} = arctan[f(x)] + c);
thus, first, multiply and divide the remaining integrals by 2:
[1/(42)] ln [(x+2x +1)/(x-2x +1)] + (1/4)(2) dx/[2(x+2x +1)] +
(1/4)(2) dx/ [2(x-2x +1)] =
[1/(42)] ln [(x+2x +1)/(x-2x +1)] + (1/2) dx/(2x+22x +2) +
(1/2) dx/ (2x-22x +2) =
(rewriting 2 as 1+1)
[1/(42)] ln [(x+2x +1)/(x-2x +1)] + (1/2) dx/(2x + 22x +1 +1) +
(1/2) dx/ (2x- 22x +1 + 1) =
[1/(42)] ln [(x+2x +1)/(x-2x +1)] + (1/2) dx/[(2x + 22x +1) +1] +
(1/2) dx/ [(2x- 22x +1) +1] =
having completed the squares,
[1/(42)] ln [(x+2x +1)/(x-2x +1)] + (1/2) dx/[(2x +1)+1] +
(1/2) dx/ [(2x -1)+1] =
finally, divide and multiply the integrals by 2:
[1/(42)] ln [(x+2x +1)/(x-2x +1)] + (1/2)(1/2) (2dx)/[(2x +1) +1] +
(1/2)(1/2) (2dx)/ [(2x -1) +1] =
so that you can rewrite the numerators as:
[1/(42)] ln [(x+2x +1)/(x-2x +1)] + [1/(22)] [d(2x +1)] /[(2x +1) +1] +
[1/(22)] [d(2x - 1)] / [(2x -1) +1] =
[1/(42)] ln [(x+2x +1)/(x-2x +1)] + [1/(22)] arctan (2x +1) +
[1/(22)] arctan (2x - 1) + c
in conclusion,

## [1/(x+ 1)] dx = [1/(42)] ln [(x+2x +1)/(x-2x +1)] +

[1/(22)] arctan (2x +1) + [1/(22)] arctan (2x - 1) + c
the next one is easier, and since you were able to solve it yourself, I won't show its solution,
which needs factoring (x-1) completely and then proceeding with usual partial fraction
decomposition
I hope it has been helpful...
Bye and good luck!